Homens com T maiúsculo: processos de identificação e construção do corpo nas transmasculinidades - Rafaela Vasconcelos Freitas (2014)
The present work sought to present the processes of identification and construction of masculinity in transsexual men, focusing on their relations with the body and their lives of sexuality. In this context of appearance and visibility, the internet is presented as a propitiating and regulatory context. Able to materialize and humanize an identity marked by pathologization and at the same time represent as normative regulations. For that, a package of actions was carried out in two discussion groups of transsexual men on the web, as well as semi-structured interviews with six transsexual men. It was verified that as transmasculinities they intend an extension of the idea of masculine and denounce like regulations imposed to bodies designated as feminine. The processes of solidarity among peers and the production and dissemination of information through the Internet appear as fundamental in the humanization of the transsexual experience, as well as providing an unprecedented political articulation of the segment and its insertion in national policies.